STRATEGI PENGEMBANGAN BISNIS SALAD BUAH LUMER DENGAN ANALISIS SWOT - Yahya, Irfan Maulana (Cahaya Ilmu Bangsa, 2024)
Analysing and building business development strategies for lumer fruit, as well as creating sales strategies to develop fruit salad business using SWOT and BMC analysis methods as a benchmark to identify the strengths, weaknesses, opportunities and threats of any kind that will be present if you want to start fruit salads business. The ultimate task is to use the SWOT analysis method as a means of formulating and implementing the development of a business on lumer fruit salad, to make a business that is thriving and has a good marketing strategy and economic calculation and is experiencing an increase every year. Based on the results and discussions that have been made then this final task can be concluded that the development of the business strategy of Salad Fruit Lumer should implement the above development strategy. An analysis of internal and external factors showed that the strength factor (S) has a score of 1.78 and the weakness factor (W) has the score of 0.74. Whereas the chance factor (O) scores 1.71 and the threat factor (T) scored 0.96. The overall score of the Internal Strategy Factor Analysis (IFAS) achieved a score of 2.52. This indicates that Lumer Fruit Salad has a great power to face the opportunities and threats that arise, the total score of external strategy factor analysis (EFAS) that has been carried out degradation and rating of 2.67. Indicates that Lumer Fruit Salad is sufficiently responsive or responsive to the opportunities and threats that occur. In addition, Lumer fruit salad needs to create a system in ordering or selling as well as clarify the jobdesk to make it easier to do the work on Lumer Salad. All of these strategies are allocated to SWOT and BMC analysis strategies that are all elements. Keywords : Business Development Strategis, Busines Strategis, SWOT Analysis